2006
DOI: 10.1007/s00705-006-0867-z
|View full text |Cite
|
Sign up to set email alerts
|

Sobemoviruses possess a common CfMV-like genomic organization

Abstract: Based on structural differences in the ORF2 region, the sobemoviruses have been subdivided into southern cowpea mosaic virus (SCPMV)-like and cocksfoot mottle virus (CfMV)-like types of genome organization. However, nearly identical amino acid sequences are encoded by these subgroups in different reading frames of ORF2, suggesting that insertion or deletion of appropriate nucleotides could restore similar genomic organizations for these viruses. We resequenced the regions of inconsistency for isolates of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…1a) while, in other sobemoviruses, ORFs 2a and 2b were thought to be fused into a single long ORF, with the overlap region between ORFs 2a and 2b comprising a third ORF that might be accessed via ribosomal frameshifting. However, Meier and Truve (2007) demonstrated that in fact there was no such variation and all sobemoviruses conform to the genome organization displayed in Fig. 1a.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…1a) while, in other sobemoviruses, ORFs 2a and 2b were thought to be fused into a single long ORF, with the overlap region between ORFs 2a and 2b comprising a third ORF that might be accessed via ribosomal frameshifting. However, Meier and Truve (2007) demonstrated that in fact there was no such variation and all sobemoviruses conform to the genome organization displayed in Fig. 1a.…”
Section: Introductionmentioning
confidence: 78%
“…Most have complete or near-complete coverage of the virus genome, but partial sequence Z36903 was removed as it has 100% nucleotide identity to a subsequence of Z48630. Several early sobemovirus sequences have significant sequencing errors, in particular with regards to the frameshift configuration of ORFs 2a and 2b (Meier and Truve, 2007). The following sequences have ORFs 2a and 2b incorrectly fused into a single long ORF: AB040446, AF055887, AF055888, L20893, L34672, U23142, U31286 and M23021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobemoviruses are transmitted by beetle vectors, seeds and direct contact [18]. They share a common genomic organization, as found after re-sequencing some of the virus species [19],[20]. Ten sobemovirus species have been fully sequenced, nine of them are currently registered by ICTV [18] and a tentative one, Imperata yellow mottle virus (IYMV), was recently isolated from Imperata cylindrica in Africa [56].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that SeMV polyprotein 2a has a domain arrangement of membrane anchor (MA)-protease-VPg-p10-p8 [11]. The polyprotein 2ab that is translated by a −1 ribosomal frame shift mechanism has a domain arrangement of MA-protease-VPg-RdRp [11], [12]. The polyproteins 2a/2ab were predicted to contain an N-terminal transmembrane domain (70 residues from N-terminus) and a cleavage site was identified at residue 132 [11], [13].…”
Section: Introductionmentioning
confidence: 99%